2018
DOI: 10.1111/imm.12942
|View full text |Cite
|
Sign up to set email alerts
|

Early programming and late‐acting checkpoints governing the development of CD4 T‐cell memory

Abstract: CD4 T cells contribute to protection against pathogens through numerous mechanisms. Incorporating the goal of memory CD4 T-cell generation into vaccine strategies therefore offers a powerful approach to improve their efficacy, especially in situations where humoral responses alone cannot confer long-term immunity. These threats include viruses such as influenza that mutate coat proteins to avoid neutralizing antibodies, but that are targeted by T cells that recognize more conserved protein epitopes shared by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 95 publications
(120 reference statements)
1
13
0
Order By: Relevance
“…IL-2, via regulation of Bcl-6 expression, also plays fundamental roles in memory CD4 T cell development [63][64][65]. Current dogma suggests that naïve CD4 + T cells require high levels of IL-2 to differentiate into memory precursor cells; however, these precursor cells are then dependent on low levels of IL-2 to develop into long-lived memory cells.…”
Section: T-bet the Master-regulator Of Th1 Cells Acts In An Expressmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-2, via regulation of Bcl-6 expression, also plays fundamental roles in memory CD4 T cell development [63][64][65]. Current dogma suggests that naïve CD4 + T cells require high levels of IL-2 to differentiate into memory precursor cells; however, these precursor cells are then dependent on low levels of IL-2 to develop into long-lived memory cells.…”
Section: T-bet the Master-regulator Of Th1 Cells Acts In An Expressmentioning
confidence: 99%
“…Although CD4 + TRM were reported to express low levels of T-bet [62], suggesting that this pathway is dispensable for CD4 TRM maintenance, future work should investigate the role of T-bet-promoting cytokines for regulating CD4 + TRM development, since this has not yet been fully resolved. IL-2, via regulation of Bcl-6 expression, also plays fundamental roles in memory CD4 T cell development [63][64][65]. Current dogma suggests that naïve CD4 + T cells require high levels of IL-2 to differentiate into memory precursor cells; however, these precursor cells are then dependent on low levels of IL-2 to develop into long-lived memory cells.…”
Section: T-bet the Master-regulator Of Th1 Cells Acts In An Expressmentioning
confidence: 99%
“…In fact, IL‐15 was shown to be essential for these IL‐2‐independent cells, acting as an ‘alarm’ at local sites of infection to promote both CD8 + T‐cell responses and induce long‐lived CD4 + T RM. Using fluorescently labelled antibody injection, Hondowicz et al . showed that LCMV‐specific CD4 + T‐cells migrated to the lungs as a Tbet hi T H 1 subset with CD69 expression similar to influenza experiments.…”
Section: Tissue‐resident Cd4+ Memory T‐cellsmentioning
confidence: 95%
“…A recent comprehensive review of studies aimed at resolving the signals required for CD4 + memory T‐cell formation discussed the instructive signals both during the ‘early priming’ phase of initial antigen recognition and activation as well as at ‘late‐acting checkpoints’ prior to contraction that play a role in the effector‐to‐memory transition. Much like the signals important for CD8 + memory T‐cell generation, strengths of TCR and co‐stimulatory signalling also have profound effects on memory T H development . Recent results from Snook et al .…”
Section: Cd4+ T‐cell Memory In Secondary Lymphoid Organsmentioning
confidence: 99%
See 1 more Smart Citation